Mythology and diplomacy in the Age of Exploration - Knobler, Adam (European expansion and indigenous response ;, 2017)
This book examines the relationship between medieval European mythologies of the non-Western world and the initial Portuguese and Spanish voyages of expansion and exploration to Africa, Asia and the Americas. From encounters with the Mongols and successor states, to the European contacts with Ethiopia, India and the Americas, as well as the concomitant Jewish notion of the Ten Lost Tribes, the volume views the Western search for distant, crusading allies through the lens of stories such as the apostolate of Saint Thomas and the stories surrounding the supposed priest-king Prester John. In doing so, Knobler weaves a broad history of early modern Iberian imperial expansion within the context of a history of cosmologies and mythologies.